2009
DOI: 10.1096/fj.08-126383
|View full text |Cite
|
Sign up to set email alerts
|

RAGE regulates BACE1 and Aβ generationviaNFAT1 activation in Alzheimer's disease animal model

Abstract: The receptor for advanced glycation end products (RAGE) is a multiligand cell surface receptor, and amyloid beta peptide (Abeta) is one of the ligands for RAGE. Because RAGE is a transporter of Abeta from the blood to the brain, RAGE is believed to play an important role in Alzheimer's disease (AD) pathogenesis. In the present study, the role of RAGE in Abeta production was examined in the brain tissue of an AD animal model, Tg2576 mice, as well as cultured cells. Because beta-site APP-cleaving enzyme 1 (BACE1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
83
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 51 publications
7
83
0
Order By: Relevance
“…Notably, RAGE expression upregulates severalfold in cerebral vessels, microglia, and neurons that are affected in human AD brains and rodent AD model brains (Zlokovic, 2008). Several studies, including our previous report, have shown that RAGE levels rise with age in rodents and humans (Simm et al, 2004;Cho et al, 2009). In addition, RAGE expression in neurons and human brain microvascular endothelial cells is increased on treatment with A␤ (Cho et al, 2009;Li et al, 2009).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Notably, RAGE expression upregulates severalfold in cerebral vessels, microglia, and neurons that are affected in human AD brains and rodent AD model brains (Zlokovic, 2008). Several studies, including our previous report, have shown that RAGE levels rise with age in rodents and humans (Simm et al, 2004;Cho et al, 2009). In addition, RAGE expression in neurons and human brain microvascular endothelial cells is increased on treatment with A␤ (Cho et al, 2009;Li et al, 2009).…”
Section: Discussionmentioning
confidence: 75%
“…Several studies, including our previous report, have shown that RAGE levels rise with age in rodents and humans (Simm et al, 2004;Cho et al, 2009). In addition, RAGE expression in neurons and human brain microvascular endothelial cells is increased on treatment with A␤ (Cho et al, 2009;Li et al, 2009). Figure 4 shows that RAGEoverexpressing bEnd.3 cells experience greater reductions in ZO-1 levels during treatment with A␤.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Multiple mechanisms are recently proposed to mediate the upregulation of BACE1 associated with AD. Those include the increased phosphorylation of the translation initiation factor eIF2a Devi and Ohno, 2010b;O'Connor et al, 2008), caspase-3-dependent inactivation of GGA3 leading to decreased lysosomal degradation of BACE1 (Sarajarvi et al, 2009;Tesco et al, 2007), changes in microRNA expression profiles (Hebert et al, 2008;Wang et al, 2008), p25/cyclin-dependent kinase 5 pathways (Cruz et al, 2006;Wen et al, 2008), calpain activation (Liang et al, 2010), the receptor for advanced glycation end products (RAGE) (Cho et al, 2009;Guglielmotto et al, 2010), and oxidative stress or related signals such as nuclear factor-kB, c-Jun N-terminal kinase, and p38 MAPK (Chen et al, 2011;Chen et al, 2008;Coma et al, 2008;Xiong et al, 2007). Further study will be needed to determine the molecular pathways by which activation of BDNF-TrkB signaling may counteract the BACE1 elevation in 5XFAD mice.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic accumulation of AGEs is accelerated with aging and with aging‐related diseases such as diabetes, hyperlipidemia, and renal disease (Cho et al ., 2009). Advanced glycation end products AGEs may accumulate in vascular tissues, thickening and stiffening vascular walls, and increasing the risk of hypertension (Singh et al ., 2001; Goh & Cooper, 2008).…”
Section: Introductionmentioning
confidence: 99%